Description and phylogenetic placement of a new species of Patania (Lepidoptera: Crambidae: Spilomelinae) resembling P. harutai (Inoue, 1955) - Matsui, Yuki; Naka, Hideshi (Zootaxa, 2023)
Patania harutai (Inoue, 1955) was known to be the mixture of two species that use host plants from two different families, Styracaceae and Sapindaceae, but the type materials had not been examined until now. In this study, we confirm the identity of P. harutai based on the adult external characters of the holotype. As a result, we regard the Sapindaceae-feeding species to be true P. harutai, and describe the Styracaceae-feeding species as a novel species, P. crepuscularia sp. nov. Patania gorosoe Lee, Heo & Bae, 2022 syn.n. is treated as a junior synonym of P. harutai. In addition, we conducted a molecular phylogenetic analysis using 10 Japanese Patania species, and found that P. crepuscularia and P. harutai are not sister species although they are very similar in the adult external characters.